Comparative studies on non-convex optimization methods for transmission network expansion planning - Gallego, R. A.; Monticelli, A.; Romero, R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
We have investigated and extensively tested three families of non-convex optimization approaches for solving the transmission network expansion planning problem: simulated annealing (SA), genetic algorithms (GA), and tabu search algorithms (TS). The paper compares the main features of the three approaches and presents an integrated view of these methodologies. A hybrid approach is then proposed which presents performances which are far better than the ones obtained with any of these approaches individually. Results obtained in tests performed with large scale real-life networks are summarized.
Keywords: Combinatorial optimization; Genetic algorithm; Network static expansion planning; Simulated annealing; Tabu search